Novel Strategy for the Development of Antibacterial TiO(2) Thin Film onto Polymer Substrate at Room Temperature - Phuinthiang, Patcharaporn (Nanomaterials (Basel), 2021)
This work demonstrates a novel method to deposit an antibacterial TiO(2) thin film on a polymer substrate at room temperature. A combination of sol–gel and photon assistance was used in the experiment in order to avoid any thermal processes of thin film crystallization. The morphological photograph of samples indicated that the TiO(2) thin film was perfectly coated on the PVC substrate without any cracks or pinholes. Chemical analysis by EDS and XPS reported that the thin film consisted of titanium (Ti), oxygen (O), and carbon (C). The Raman spectrum proved that the thin film was the anatase phase of TiO(2) and, furthermore, that it was contaminated with carbon remaining from the photon assistance process. In addition, the optical band gap of the thin film was 3.35 eV, suggesting that the photocatalytic activity of TiO(2) should occur under UV-A radiation. The bacteria viability assay was examined using E. coli and S. typhimurium as indicator strains under UV-A irradiation (365 nm) at different times. The data from OD and CFU count revealed that >97% of bacteria were killed after 60 min of irradiation, and the bacteria were completely killed at 120 min for E. coli and 180 min for S. typhimurium.